A few potholes on the road to salvation: Codes of ethics in adult education - Thomas J. Sork (Adult Education Research Conference, 1996)
This paper presents a critical analysis of two ethical codes and a set of guidelines for developing ethical codes that present principles intended to guide adult education practitioners. The analysis suggests that these initial efforts, although laudable in intent, have serious flaws that must be corrected if codes of ethics are to be viewed by practitioners as useful and credible statements of their ethical obligations.